IMPLEMENTASI BAURAN PEMASARAN SEBAGAI STRATEGI PEMASARAN TOKO EMAS SUMBER MULIA ARGAMAKMUR DALAM MENINGKATKAN JUMLAH PELANGGAN - Endang Lestari, Dwi; Fajarini, Sri Dwi (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2024)
In marketing products or services, business actors must develop products or services that are unique compared to their competitors. Therefore, a good marketing strategy is needed to increase the number of consumers who are interested in marketing products, including precious metals or gold. This research was conducted to better understand the application of the marketing mix as part of the marketing communication strategy implemented by Sumber Mulia Gold Shop, Argamakmur, North Bengkulu to market its products and services in order to increase the number of customers. This research uses Kotler and Armstrong's theory with a qualitative descriptive research method with data collection using interviews, observations and documents. With the informant selection technique using purposive sampling. The results of this research show that the marketing communication activities carried out by the Sumber Mulia Argamakmur Gold Shop have the characteristics of a jewelry business in the form of necklaces, rings, bracelets and earrings that are beautiful and attractive to wear. Apart from that, Sumber Mulia Gold Shop offers its products at prices that are cheaper than other shops in Arga Makmur, North Bengkulu. In terms of promotions, Sumber Mulia Gold Shop follows modern developments, namely carrying out promotions through the WhatsApp story feature and the Facebook story feature with images and Attractive advertising captions and strategic product sales locations. Keywords :Marketing Mix, Sumber Mulia Gold Shop, marketing communications, consumers